Nonlinear Targeted Energy Transfer in Mechanical and Structural Systems - Vakakis, Alexander F. (Springer, 2017)
Introduces to the international literature the new concept of targeted nonlinear energy transfer, whereby unwanted vibration energy is transferred to preferential directions within a system, or to structural modes that are compatible to a set of requirements or design objectives Such a concept is novel and has vast applications to diverse fields of engineering, applied mechanics, and applied physics/mathematics.